Chondrogenic differentiation of human bone marrow MSCs in osteochondral implants under kinematic mechanical load is dependent on the underlying osteo component - Monaco, Graziana; Qawasmi, Feras; El Haj, Alicia J.; Forsyth, Nicolas R.; Stoddart, Martin J. (Frontiers in Bioengineering and Biotechnology, 2022)
Chondrogenic models utilizing human mesenchymal stromal cells (hMSCs) are often simplistic, with a single cell type and the absence of mechanical stimulation. Considering the articulating joint as an organ it would be beneficial to include more complex stimulation. Within this study we applied clinically relevant kinematic load to biphasic constructs. In each case, the upper layer consisted of fibrin embedded hMSCs retained within an elastomeric polyurethane (PU) scaffold. These were randomly assigned to five base scaffolds, a cell-free fibrin PU base, viable bone, decellularized bone, 3D printed calcium phosphate or clinically used cement. This allowed the study of cross talk between viable bone and chondrogenically differentiating MSCs, while controlling for the change in stiffness of the base material. Data obtained showed that the bulk stiffness of the construct was not the defining factor in the response obtained, with viable and decellularized bone producing similar results to the softer PU base. However, the stiff synthetic materials led to reduced chondrogenesis and increased calcification in the upper MSC seeded layer. This demonstrates that the underlying base material must be considered when driving chondrogenesis of human cells using a clinically relevant loading protocol. It also indicates that the material used for bony reconstruction of osteochondral defects may influence subsequent chondrogenic potential.